1996
DOI: 10.1021/ic950540a
|View full text |Cite
|
Sign up to set email alerts
|

Mobility of Copper in Binding Sites in Rabbit Liver Metallothionein 2

Abstract: We describe the first direct evidence for mobility of Cu(I) atoms within the metal binding sites in mammalian metallothionein based on temporal changes in the emission spectrum of Cu n -MT (n ) 1-20) in the 600 nm region. The emission intensities are specifically dependent on the temperature and on the metal:protein molar ratio between 1 Cu(I), 12 Cu(I), and 20 Cu(I) [

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…The relatively high compactness protected the metal ions from the solvent intrusion. All of these findings were consistent with the previous research reports (Green and Stillman ; Vergani and others ).…”
Section: Resultssupporting
confidence: 93%
“…The relatively high compactness protected the metal ions from the solvent intrusion. All of these findings were consistent with the previous research reports (Green and Stillman ; Vergani and others ).…”
Section: Resultssupporting
confidence: 93%
“…The temperature dependence of the luminescence properties of Cu(I) MT-2, coupled with examination of the CD spectra, revealed information on the modes of binding of Cu(I) to MT-2 . It was found that the α domain emitted much more intensely than its β counterpart in MT-2.…”
Section: B Copper(i) In Metallothionein Proteinsmentioning
confidence: 99%
“…22,100 Experimental evidence directly disputes this last requirement, as displacement of Zn 2+ from Zn 7 -MT by Cu + occurs in a distributive manner (binding to both domains) followed by a time-and temperature-dependent rearrangement leading to the expected metal ion selectivity. 132,133 It is possible that MT is able to achieve metal ion equilibrium through both the bead-model structure mechanism and through these supermetallated states. Briefly the coordination of an exogenous metal ion to Zn 7 -MT, such as Cd 2+ or Cu + , leads to the transient formation of a (Cd or Cu) 1 Zn 7 -MT followed by a rearrangement and subsequent expulsion of one of the previously bound Zn 2+ ions to form (Cd or Cu) 1 Zn 6 -MT with the expected metal ion specificity.…”
Section: Single Domains: Supermetallation Of Mtmentioning
confidence: 99%